Rhenium(Vii) Extraction from Sulfuric Aqueous Solutions Using Ionic Liquids as Diluent and Extractant: Insights on the Extraction Stoichiometry and Process Parameters - Romero-Figueroa, J; Quijada-Maldonado, E; Araya-Lopez, C; Olea-Chandia, F; Villarroel-Utreras, E (John Wiley and Sons Ltd, 2022)
BACKGROUND: Rhenium(Re) is a highly valuable metal recovered from molybdenite leach liquors by solvent extraction (SX) using toxic organic solvents. This work proposes an extracting phase free of volatile organics composed by the ionic liquid (IL) trioctylmethylammonium benzoate [TOMA][BA] as the extractant, due to its ability to extract Re(VII), and the IL 1-octyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [omim][Tf2N] as the diluent, due to its high hydrophobicity where the extraction stoichiometry and process parameters such as the initial pH, the extractant concentration in the diluent and stripping using ammonium hydroxide ((Formula presented.)) and sodium hydroxide ((Formula presented.)) were assessed. RESULTS: This extracting phase yielded high extraction percentages: 95% with only 3% (v/v) of [TOMA][BA] in [omim][Tf2N]. A detailed study of the SX stoichiometry was carried out through slope analysis, showing that the SX occurs in two steps: first, the extraction of acid; then, the extraction of the metal ion via anion exchange with the transfer of IL-diluent anion to the aqueous phase. Additionally, the extracting phase was tested in a synthetic molybdenite leached pregnant leach solution, showing selectivity towards Re(VII) over Cu(II) and Fe(III) at very low extractant concentration. The stripping of Re(VII) from the loaded phase was also studied achieving 60% stripping in only one equilibrium step when using (Formula presented.). CONCLUSION: This novel extracting phase, free of volatile organic, shows promising Re(VII) extraction for future industrial applications. © 2021 Society of Chemical Industry (SCI). © 2021 Society of Chemical Industry (SCI).